Survey of intention recognition for opponent modeling - Wei GAO; Junren LUO; Weilin YUAN; Wanpeng ZHANG (网络与信息安全学报)
Several different methods of opponent modeling were introduced, leading to the problem of intention recognition in behavior modeling.Then, the process, classification, main methods, research prospects and practical applications of intention recognition were analyzed inductively, the latest research in related fields were summarized.Finally, some shortcomings of the current intention recognition and design methods were pointed out and some new insights for the future research were presented.